2022
DOI: 10.3389/fevo.2022.934054
|View full text |Cite
|
Sign up to set email alerts
|

Midgut Bacterial Communities of Vespa velutina Lepeletier (Hymenoptera: Vespidae)

Abstract: Vespa velutina nigrithorax and Vespa velutina auraria are two subspecies of Vespa velutina Lepeletier. V. velutina preys managed honey bees, other pollinators, and insects. However, the Vespa midgut microbiota of three forms, namely queens, workers, and males have not been reported, thus the objective of this study was to analyze the midgut bacterial diversity of the three forms of V. v. nigrithorax and V. v. auraria. Our results showed that Proteobacteria, Firmicutes, Bacteroidetes, Tenericutes, and Actinobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Our study provided a comprehensive description of the cultivable bacterial community of the crop, midgut and hindgut compartments, as well as the ovaries of the invasive hornet V. velutina . While these results were obtained through the analysis of samples from a single nest of Asian hornets in Belgium, they were largely congruent with 16S rRNA amplicon sequencing data reported in Italy (Cini et al, 2020) and China (Zhang et al, 2022). The results obtained suggested that the Asian hornet bacterial community was dominated by Convivina , Fructobacillus , Lactococcus , Sphingomonas , Spiroplasma and Lactiplantibacillus .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study provided a comprehensive description of the cultivable bacterial community of the crop, midgut and hindgut compartments, as well as the ovaries of the invasive hornet V. velutina . While these results were obtained through the analysis of samples from a single nest of Asian hornets in Belgium, they were largely congruent with 16S rRNA amplicon sequencing data reported in Italy (Cini et al, 2020) and China (Zhang et al, 2022). The results obtained suggested that the Asian hornet bacterial community was dominated by Convivina , Fructobacillus , Lactococcus , Sphingomonas , Spiroplasma and Lactiplantibacillus .…”
Section: Discussionsupporting
confidence: 86%
“…We subsequently compared the results obtained with those of a 16S rRNA amplicon sequencing analysis of samples of the same nest to provide a more complete image of these bacterial communities, as both approaches have intrinsic biases and limitations (Duthoo et al, 2022; Hong et al, 2009; Lagier et al, 2012; O'Callaghan et al, 2021). Both cultivation‐independent and cultivation‐dependent approaches revealed a dominant occurrence of Bacillota and Pseudomonadota in the hornet's gut microbiota, which was consistent with results from other insect species (Yun et al, 2014), other hornet species (Suenami et al, 2019) and two recent studies of V. velutina (Cini et al, 2020; Zhang et al, 2022). While 16S rRNA gene amplicon sequencing revealed a different gut microbiota composition in each of the sample types (i.e., gut fractions and ovaries), each sample type displayed a similar richness and diversity (Figure S1).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The gut bacterial communities in the five Vespa species predominantly consisted of Proteobacteria, accompanied by Firmicutes and Bacteroidetes, aligning with previous studies. 31 Inter-species differences in gut bacterial composition at the phylum level may bear ecological and physiological implications. We observed a higher relative abundance of Firmicutes in V. velutina and V. mandarinia than in V. analis, V. crabro, and V. ducalis.…”
Section: Discussionmentioning
confidence: 99%